Antibacterial and antibiofilm activities of Swietenia macrophylla king ethanolic extract against foodborne pathogens - Che Amira Izzati Che Man,; Wan Razarinah Wan Abdul Razak,; Mohd Fakharul Zaman Raja Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Swietenia macrophylla is known to possess several medicinal uses, however, its antibacterial and antibiofilm activities against foodborne pathogens remain not well investigated. The present work was performed to examine the phytochemical compounds, antibacterial and antibiofilm activities of S. macrophylla ethanolic extract (SMEE) against four foodborne pathogens namely, Salmonella typhimurium ATCC 14028, Escherichia coli ATCC 25922, Shigella sonnei ATCC 33862 and Pseudomonas aeruginosa ATCC 10145. The phytochemical analysis of SMEE was performed using gas chromatography-mass spectrometry while the antibacterial activities of SMEE were determined by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays. On the other hand, the antibiofilm and time-killing activities of SMME were evaluated using a crystal violet assay. The result demonstrated that SMEE contained major phytochemical compounds such as olean-12-ene (27.37%), resorcinol (16.45%), 24-noroleana-3,12-diene (13.4%), and germanicol (11.50%). The MIC values of SMEE ranged from 31.25 to 500 μg/mL, while all the MBC values were found to be greater than 1000 μg/mL. At the 12 h exposure to SMEE, all the biofilms were inhibited by 50% except E. coli. Biofilm inhibitory concentration (BIC50) values of SMEE ranged between 5.19 and 42.47 μg/mL. In conclusion, S. macrophylla is a promising source of natural antibacterial and antibiofilm agents to treat foodborne diseases.